Nickel Hilirization as Added Value in Strengthening Indonesia's Economy - Audrey G. Tangkudung; Jemmi Y. Kaseger (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Indonesia is one of the countries that has the largest nickel reserves in the world. In addition to nickel being used for export, currently the government has made it mandatory to downstream nickel domestically. Besides that, the potential for nickel in Indonesia also plays a role in increasing investment for state revenue, through smelter investments. Through the nickel export ban policy, the continuity of the supply of crude nickel in the long term for the needs of domestic smelters is maintained. But there are issues in society due to the export ban affecting the selling price of nickel, especially impacting business activities. This paper discusses the extent of the downstream nickel policy, the ban on nickel ore exports, the added value obtained and the obstacles faced. The research method used is explorative and descriptive method, Data collection for analysis purposes, among others, was obtained from various literature, regulations and laws and regulations, media coverage and various other relevant secondary data sources.The findings show that nickel downstream actually creates added value and pushes nickel prices in a positive direction, thus encouraging investors to come to Indonesia thereby strengthening the Indonesian economy in a better direction.